Students’ Preferences on Online-Based Media for Writing Course and the Reasons - Wahyunengsih Wahyunengsih; Dewi Sekar Arum; Miftakhul Jannah; Nuraffah Irtiyah; Siska Anggraeni; Avita Ayu Permana Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This article aims to investigate students’ point of view about the most preference on online writing course media and their reasons. The methodology used was qualitative research method. The instrument was the questionnaires that were given to 34 students of Writing Course. They were in the fourth semester majoring in English Teaching. The finding showed the various type of applications and digital technology for learning in synchronous class such as, zoom, Google meet, Facebook, and Whatsapp Chat video. The Social media and translation machines take place as the most preferable online media for writing course. In choosing learning media, teachers must consider the learners’ previous knowledge related to technological skills as well as the practicality of the media. There are plenty of sophisticated online media of writing nowadays, but without having a good research on students’ preferences, it will be worthless.